Combining Immunotherapy with Oncogene-Targeted Therapy: A New Road for Melanoma Treatment - Aris, Mariana; Barrio, María Marcela (Frontiers in Immunology, 2015)
Cutaneous melanoma arises from the malignant transformation of skin melanocytes; its incidence and mortality have been increasing steadily over the last fifty-years, now representing 3% of total tumors. Once melanoma metastasizes, prognosis is somber and therapeutic options are limited. However, the discovery of prevalent BRAF mutations in at least 50% of melanoma tumors led to development of BRAF inhibitors, and other drugs targeting the MAPK pathway including MEK inhibitors, are changing this reality. These recently approved treatments for metastatic melanoma have made a significant impact on patient survival; though the results are shadowed by the appearance of drug-resistance. Combination therapies provide a rational strategy to potentiate efficacy and potentially overcome resistance. Undoubtedly, the last decade has also born an renaissance of immunotherapy, and encouraging advances in metastatic melanoma treatment are illuminating the road. Immune checkpoint blockades, such as CTLA-4 antagonist-antibodies, and multiple cancer vaccines are now invaluable arms of anti-tumor therapy. Recent work has brought to light the delicate relationship between tumor biology and the immune system. Host immunity contributes to the antitumor activity of oncogene-targeted inhibitors within a complex network of cytokines and chemokines. Therefore, combining immunotherapy with oncogene-targeted drugs may be the key to melanoma control. Here we review ongoing clinical studies of combination therapies using both oncogene inhibitors and immunotherapeutic strategies in melanoma patients. We will revisit the preclinical evidence that tested sequential and concurrent schemes in suitable animal models and formed the basis for the current trials. Finally, we will discuss potential future directions of the field.